Quality Improvement in Neurology: Dementia Management Quality Measures. Issue 3 (7th January 2014) - Odenheimer, Germaine; Borson, Soo; Sanders, Amy E.; Swain‐Eng, Rebecca J.; Kyomen, Helen H.; Tierney, Samantha; Gitlin, Laura; Forciea, Mary Ann; Absher, John; Shega, Joseph; Johnson, Jerry
<x xml:space="preserve">Abstract</x> Professional and advocacy organizations have long urged that dementia should be recognized and properly diagnosed.12 With the passage of the National Alzheimer's Project Act3 in 2011, an Advisory Council for Alzheimer's Research, Care, and Services was convened to advise the Department of Health and Human Services. In May 2012, the Council produced the first National Plan to address Alzheimer's disease, and prominent in its recommendations is a call for quality measures suitable for evaluating and tracking dementia care in clinical settings.4 Although other efforts have been made to set dementia care quality standards, such as those pioneered by RAND in its series Assessing Care of Vulnerable Elders (ACOVE), 5 practitioners, healthcare systems, and insurers have not widely embraced implementation. This executive summary (full manuscript available at www.neurology.org) reports on a new measurement set for dementia management developed by an interdisciplinary Dementia Measures Work Group (DWG) representing the major national organizations and advocacy organizations concerned with the care of individuals with dementia. The American Academy of Neurology (AAN), the American Geriatrics Society, the American Medical Directors Association, the American Psychiatric Association, and the American Medical Association–convened Physician Consortium for Performance Improvement led this effort. The ACOVE measures and the measurement set described here apply to individuals whose dementia has already been identified and properly diagnosed. Although similar in concept to ACOVE, the DWG measurement set differs in several important ways; it includes all stages of dementia in a single measure set, calls for the use of functional staging in planning care, prompts the use of validated instruments in patient and caregiver assessment and intervention, highlights the relevance of using palliative care concepts to guide care before the advanced stages of illness, and provides evidence‐based support for its recommendations and guidance on the selection of instruments useful in tracking patient‐centered outcomes. It also specifies annual reassessment and updating of interventions and care plans for dementia‐related problems that affect families and other caregivers as well as individuals with dementia. Here, a brief synopsis of why major reforms in healthcare design and delivery are needed to achieve substantive improvements in the quality of care is first provided, and then the final measures approved for publication, dissemination, and implementation are listed.